2019
DOI: 10.3390/w11071432
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the Relative Contribution of Environmental Factors to Runoff Change in the Headwaters of the Yangtze River

Abstract: The change in river flows at the basin scale reflects the combined influences of changes in various environmental factors associated with climatic and underlying surface properties. Distinguishing the relative contribution of each of these factors to runoff change is critical for sustainable water resource management, but it is also challenging. The headstream region of the Yangtze River, known as “China’s Water Tower”, has undergone a significant runoff change over the past decades. However, the relative cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Attribution analysis showed that other environmental factors contributed between −5% and 40%, and the contribution of this part comes from glaciers permafrost and human activities. The SRYZ has the highest concentration of glaciers and permafrost in China, accounting for 0.95% and 75% of the whole basin area, respectively [6]. In recent decades, the temperature in the SRYZ increased significantly, with an increase of 0.6 • C/10a, which was about four times of the global mean [48].…”
Section: Influencing Factors Of Runoff In the Sryzmentioning
confidence: 99%
See 2 more Smart Citations
“…Attribution analysis showed that other environmental factors contributed between −5% and 40%, and the contribution of this part comes from glaciers permafrost and human activities. The SRYZ has the highest concentration of glaciers and permafrost in China, accounting for 0.95% and 75% of the whole basin area, respectively [6]. In recent decades, the temperature in the SRYZ increased significantly, with an increase of 0.6 • C/10a, which was about four times of the global mean [48].…”
Section: Influencing Factors Of Runoff In the Sryzmentioning
confidence: 99%
“…Climate change has had significant effect on the water cycle in the basin through factors such as precipitation, temperature, sunshine, wind speed, etc. [5,6], with precipitation being the crucial driving factor [7]. In addition, with rapid economic development, human activities are altering the ecological environment of a basin in the form of greenhouse gas emissions, land-use changes, water conservancy construction, and human water consumption, resulting in an increasingly significant effect on river runoff [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the assumption of S = 0 may not hold, especially in small basins [53,73]. Small basins often have frequent water exchange with neighboring basins, and ignoring this part of the water may result in a large bias in ET estimation from the water balance method [74].…”
Section: Potential Uncertainty Sourcesmentioning
confidence: 99%
“…Increased drought frequency and intensity since 1995 is likely due to the effects of climate change. With global warming, the Earth's climate system becomes more unstable than ever before [44], causing drought events to become more frequent in many regions of the world [45][46][47].…”
Section: Drought Patterns At Different Timescalesmentioning
confidence: 99%